Bad Kitty Goes on Vacation - Bruel, Nick (New York : Roaring Brook Press, 2020)
"Kitty's life is still hard. Really, really, really hard. She's always being bothered, Puppy is always in her space (and drooling on her), and her plans for world domination seem to be at a bit of a stand still. So, when she gets the opportunity to go with her very favorite, generous, kind-hearted Uncle Murray to LOVE LOVE ANGEL KITTY WORLD, how on earth could she refuse?"--Provided by publisher.
Keywords: Bad Kitty -- (Fictitious character from Nick Bruel) -- Juvenile fiction; Bad Kitty -- (Fictitious character from Nick Bruel) -- Fiction; Cats -- Juvenile fiction; Vacations -- Juvenile fiction; Cats -- Fiction; Vacations -- Fiction; Humorous stories; Humorous fiction